ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA PADA MATERI TRIGONOMETRI BERDASARKAN KEMAMPUAN AWAL MATEMATIS SISWA - Nadia Putri Setiana; Nelly Fitriani; Risma Amelia (IKIP Siliwangi, 2021)
This study aims to analyze the problem solving ability of high school students on trigonometry material. The method of this study is a qualitative descriptive method with the research subject of 30 students of class XI in one of the Kab. West Bandung. The data collection instrument used was in the form of a description test consisting of 4 questions with indicators of problem solving abilities. The results of student answers were analyzed using a scoring rubric which was compiled based on 4 indicators of problem solving ability, namely: 1) understanding the problem, 2) planning problem solutions, 3) implementing a settlement plan, 4) looking back. Then the data is processed by calculating the percentage of student achievement against each problem solving indicator. Based on the results of the study, it was found that students had not mastered the indicators of implementing the completion plan and looking back at the percentages 52.5% and 37.5% respectively. Students with high abilities and are making mistakes because students are less careful when solving problems with different error levels. Meanwhile, students with low abilities make mistakes due to a lack of student understanding of problems and concepts.